Dermatofibrosarcoma: report of a case with complete response to imatinib and conservative surgery during the COVID-19 pandemic - Steffen, Rafael Martins; Pacheco, Arthur Fernandes; Teixeira, Gabriela Camilo; Santos, Bruna Alejandra Orellana; Fulfaro, Marina Quaglio Oinegue; Koga, Ketleen; Ferreira, Amanda Fonseca Nunes; Cotaet, James, Junior; Zveibil, Deborah Krutman; Zapata, Rafael Ricardo da Silva Miranda (Brazilian Journal of Oncology, 2022)
Dermatofibrosarcoma protuberans (DFSP) is an extremely rare and potentially aggressive soft tissue tumor. Around 85 to 90% of DFSP cases are low-grade tumors, while the fibrosarcomatous variant (DFSP-FS) is associated with medium and high-grade neoplasms. DFSP affects more young adults, in their 30s; however, it can be present in all ages. It has a high potential for locoregional dissemination and recurrence, directly related to tumor size. In the present study, a case of dermatofibrosarcoma protuberans with local recurrence after surgical treatment will be reported, subsequently treated with imatinib and a new surgical approach, with no new recurrences so far. The effectiveness of imatinib is noted in a deep, infiltrative and relapsed DFSP, in which upfront surgery would cause significant functional and cosmetic damage. Imatinib allowed an important clinical improvement for the patient, with tumor reduction in the initial weeks of treatment.
Keywords: Dermatofibrosarcoma; Imatinib mesylate; Complementary therapies